Hubungan pekerjaan dengan perilaku pencegahan penularan tuberkulosis - Rukmana, Nova Mega; Aziza, Nurul; Liana, Safa (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Factors that can determine a person's exposure to disease/health behavior. A theoretical framework known as the Health Belief Model (HBM) is a concept used to examine factors that influence individuals in taking health actions, including tuberculosis prevention measures by TB patients. Purpose: To explore the relationship between occupation and tuberculosis prevention behavior. Method: The research design used was a quantitative study with an analytical cross-sectional method. The subjects in this study were 78 pulmonary TB patients registered in medical records in the Kedaton Community Health Center (Puskesmas) working area during the period January–June 2025. The sample selection used a total sampling method because the available population size was less than 100 respondents. Analysis was conducted using a chi-square test. Results: Of the 6 respondents who work as civil servants/ASN, there are 4 respondents (66.7%) who have good TB transmission prevention behavior, while of the 22 respondents who do not have jobs, 15 respondents (68.2%) have poor TB transmission prevention behavior. Based on the results of statistical tests, a p-value of 0.000 or p-value <0.05 was obtained. Conclusion: There is a relationship between occupation and tuberculosis prevention behavior with a p-value <0.05. Suggestion: These findings can be used as consideration by the Kedaton Community Health Center for evaluation and to help assess the extent of occupational influence in this context.   Keywords: Occupation; TB Transmission Prevention Behavior   Pendahuluan: Faktor yang dapat menentukan seseorang terpapar penyakit/perilaku kesehatan seseorang. Sebuah kerangka teori yang dikenal sebagai Health Belief Model (HBM) merupakan konsep yang dipakai untuk menelaah faktor yang memengaruhi individu dalam melakukan tindakan kesehatan, termasuk langkah pencegahan penyakit tuberkulosis oleh pasien TB. Tujuan: Untuk mengeksplorasi hubungan pekerjaan terhadap perilaku pencegahan penularan tuberkulosis. Metode: Rancangan penelitian yang digunakan adalah studi kuantitatif dengan metode cross-sectional yang bersifat analitis. Subjek dalam penelitian ini adalah pasien TB Paru yang tercatat dalam rekam medis di wilayah kerja Puskesmas Kedaton pada periode Januari–Juni 2025 berjumlah 78 orang. Pemilihan sampel memakai metode total sampling karena jumlah populasi yang tersedia dibawah 100 responden. Analisis dilakukan melalui uji chi-square. Hasil: Sebanyak 6 responden yang mempunyai pekerjaan sebagai PNS/ASN, terdapat 4 responden (66.7%) yang mempunyai perilaku pencegahan penularan TB yang baik, sedangkan dari 22 responden yang tidak mempunyai pekerjaan, dan 15 responden (68.2%) yang mempunyai perilaku pencegahan penularan TB yang kurang. Berdasarkan hasil uji statistik, didapatkan p-value 0,000 atau p-value<0.05. Simpulan: Ada keterkaitan pekerjaan dengan perilaku pencegahan penularan tuberkulosis dengan nilai p-value<0.05. Saran: Temuan ini dapat dijadikan bahan pertimbangan oleh pihak Puskesmas Kedaton untuk evaluasi sekaligus membantu menilai sejauh mana pekerjaan berpengaruh dalam konteks tersebut.   Kata Kunci: Pekerjaan; Perilaku Pencegahan Penularan TB.